Hubungan Pengetahuan Tentang Menstruasi Dengan Kesiapan Menghadapi Menarche Pada Siswi Kelas IV Sekolah Dasar - siswojo siswojo; Dwi Hendriani; Edi Purwanto (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2015)
The onset of menstruation might be a traumatic event for some young women who do not prepare themselves in advance. Deviate behavior can harm themselves because ignorance of the changes herself when have got menstrual, and they do not ready to obligation when he was menarche.This report is written with the purpose of mengeetahui relations knowledge grade student iv primary schools with better prepare for menarche in Primary Schools muhammadiyah 1 Samarinda 2012. Design of the research is analytic by cross sectional approach. The sample overall sampling on 97 respondents , the data analysis by using the t-test followed by continuity correction showed p-value = 0,001 at standard significant α = 0,05, so that it can be concluded that there is a significant relation exists between knowledge of fourth grade menstrual about with readiness face menarche in Primary School Muhammadiyah 1 Samarinda.